Radical polymerizable resin composition and molded article
The radical polymerizable resin composition, formulated with specific ratios of aliphatic (meth)acrylate, allyl ether, and bisphenol A-type epoxy (meth)acrylate, addresses the challenges of tensile elongation, heat-resistant water resistance, and air curability in non-styrene resin compositions, particularly for lining applications.
Patent Information
- Application Number
- JP2023175094
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
Non-styrene radical polymerizable resin compositions face challenges in achieving both high tensile elongation and heat-resistant water resistance, while also being susceptible to curing inhibition by air.
A radical polymerizable resin composition is developed by blending an aliphatic (meth)acrylate monomer and an allyl ether compound with an epoxy (meth)acrylate using a bisphenol A-type epoxy resin with a specific epoxy equivalent, optimizing the mass and molar ratios of the components.
The resulting resin composition exhibits excellent tensile elongation, heat-resistant water resistance, and air curability, making it suitable for lining applications without the need for styrene as a reactive diluent.
Smart Images

Figure 2025065707000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a radically polymerizable resin composition and a molded article. [Background technology]
[0002] Styrene has traditionally been used as a reactive diluent in radically polymerizable thermosetting resins, but styrene is subject to strict management under the Pollutant Release and Transfer Register (PRTR) Act, and issues such as the emission of volatile organic compounds (VOCs) arise.
[0003] In response to this, non-styrene resins that do not use styrene are being studied. The radical-polymerizable resin composition that forms the non-styrene resin does not use styrene, so it does not require the management under the PRTR Law and can be considered as one of the means to solve problems such as VOC emissions.
[0004] For example, Patent Document 1 describes a thermosetting resin composition that uses an epoxy (meth)acrylate and a (meth)acrylate monomer containing a cyclic hydrocarbon group having one carbon-carbon double bond or one nitrogen atom in the ring as a diluent, as a lining material for application to the surface of concrete, etc. in sewage treatment facilities.
[0005] Patent Document 2 describes a non-styrene type vinyl ester resin composition that uses a specific methacrylate monomer in brominated bisphenol A type epoxy (meth)acrylate and is used for coating liquid-contacting surfaces of concrete floors in factory facilities, metal tanks or pipes made of steel or stainless steel, etc., and as a matrix for fiber-reinforced resin materials, etc. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2014-95002 A [Patent Document 2] JP 2023-55303 A Summary of the Invention [Problem to be solved by the invention]
[0007] Generally, a (meth)acrylate monomer is used as a reactive diluent for a non-styrene resin that does not use styrene. However, since the dilution ability of the (meth)acrylate monomer is lower than that of styrene, there is a limit to the molecular weight of the epoxy (meth)acrylate that can be used in applications that require the resin composition to have a low viscosity.
[0008] In addition, the resin composition described in Patent Document 1 uses a specific (meth)acrylate monomer as a diluent to improve the hot water resistance (chemical resistance) of the cured resin, but the tensile elongation is low and the composition is not suitable for use in lining applications.
[0009] In addition, in the resin composition described in Patent Document 2, a brominated epoxy resin is used as a base for the epoxy (meth)acrylate resin, and thus the tensile elongation of the cured resin is good, but the hot water resistance is not satisfactory.
[0010] That is, in a resin cured product using a non-styrene resin as the matrix resin, when the tensile elongation is increased, the hot water resistance tends to decrease, and it is difficult to maintain both the tensile elongation and the hot water resistance within a good range. In addition, non-styrene resin compositions generally have the property of being easily inhibited in curing by air.
[0011] Therefore, an object of the present invention is to provide a radical polymerizable resin composition which is a non-styrene resin composition that does not use styrene as a reactive diluent, yet which can provide good properties in both tensile elongation and hot water resistance of the cured resin product, and which also has excellent air curing properties, and to provide a molded article containing the cured resin product. [Means for solving the problem]
[0012] The present inventors have found that the above-mentioned problems can be solved by blending an aliphatic (meth)acrylate monomer and an allyl ether compound with an epoxy (meth)acrylate that uses a bisphenol A type epoxy resin having a specific epoxy equivalent as a raw material.
[0013] That is, the present invention relates to the following. [1] A radical polymerizable resin composition comprising an epoxy (meth)acrylate (A), which is an ester compound made from a bisphenol A type epoxy resin and (meth)acrylic acid, an aliphatic (meth)acrylate monomer (B), and an allyl ether compound (C), wherein the bisphenol A type epoxy resin has an epoxy equivalent of 200 to 700. [2] The radical polymerizable resin composition according to [1], wherein a mass ratio [(A) / (B)] of the epoxy (meth)acrylate (A) to the aliphatic (meth)acrylate monomer (B) is 30 / 70 to 80 / 20. [3] The radical polymerizable resin composition according to [1] or [2], wherein a molar ratio of allyloxy groups derived from the allyl ether compound (C) to the sum of (meth)acryloyl groups derived from the epoxy (meth)acrylate (A) and (meth)acryloyl groups derived from the aliphatic (meth)acrylate monomer (B) [allyloxy groups / (meth)acryloyl groups] is 0.01 to 0.5. [4] The radical polymerizable resin composition according to any one of [1] to [3], wherein the aliphatic (meth)acrylate monomer (B) is an aliphatic (meth)acrylate monomer having a saturated aliphatic hydrocarbon group. [5] The radical polymerizable resin composition according to [4], wherein the aliphatic (meth)acrylate monomer (B) has 11 or less carbon atoms. [6] The radical polymerizable resin composition according to any one of [1] to [5], wherein the allyl ether compound (C) has a molecular weight of 500 or less. [7] The radical polymerizable resin composition according to any one of [1] to [6], further comprising at least one selected from a curing agent, a curing accelerator, a curing co-accelerator, and a photoradical initiator. [8] The radical polymerizable resin composition according to any one of [1] to [7], which is for hand lay-up molding. [9] A molded article comprising a cured resin product of the radical polymerizable resin composition according to any one of [1] to [8]. Effect of the Invention
[0014] According to the present invention, it is possible to provide a radical polymerizable resin composition and a molded article thereof, which is a non-styrene resin composition that does not use styrene as a reactive diluent, and yet has good properties in both tensile elongation and hot water resistance of the resin cured product, and further has excellent air curing properties. This radical polymerizable resin composition is particularly suitable for lining applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [Radical polymerizable resin composition] As described above, the radical polymerizable resin composition of the present embodiment is composed of the epoxy (meth)acrylate (A), which is an ester compound of a bisphenol A type epoxy resin and (meth)acrylic acid, the aliphatic (meth)acrylate monomer (B), and the allyl ether compound (C). Each component will be described in detail below.
[0016] <Epoxy (meth)acrylate (A)> The epoxy (meth)acrylate (A) used in this embodiment is an ester compound obtained by using a bisphenol A type epoxy resin and (meth)acrylic acid as raw materials and subjecting them to an esterification reaction.
[0017] The bisphenol A type epoxy resin used as the raw material here can be any known bisphenol A type epoxy resin without any limitation, and specific examples include glycidyl ethers synthesized by the reaction of epichlorohydrin or methylepichlorohydrin with bisphenol A; glycidyl ethers obtained by the reaction of ethylene oxide or propylene oxide adduct glycol of bisphenol A or hydrogenated bisphenol A with epichlorohydrin or methylepichlorohydrin; etc. In this specification, the bisphenol A type epoxy resin refers to an unsubstituted bisphenol A type epoxy resin or an unsubstituted hydrogenated bisphenol A type epoxy resin, and does not include, for example, brominated bisphenol A type epoxy resin. The bisphenol A type epoxy resin may be used alone or in combination of two or more kinds.
[0018] The bisphenol A type epoxy resin, which is a raw material of the epoxy (meth)acrylate resin used in this embodiment, has an epoxy equivalent (g / eq.) of 200 to 700. The epoxy equivalent of this epoxy resin affects the properties (viscosity, tensile elongation, etc.) of the resulting resin composition or cured resin.
[0019] Here, the epoxy equivalent of the bisphenol A type epoxy resin is not less than 200, preferably not less than 220, and more preferably not less than 250. By setting the lower limit of the epoxy equivalent within such a range, the viscosity of the radical polymerizable composition can be made appropriate, and the crosslinking points of the epoxy (meth)acrylate resin are prevented from becoming too numerous, thereby ensuring appropriate tensile elongation of the resin cured product.
[0020] Moreover, the epoxy equivalent is not more than 700, preferably not more than 600, and more preferably not more than 500. By setting the upper limit of the epoxy equivalent to such a numerical value, it is possible to suppress an increase in the molecular weight of the epoxy resin and an increase in the viscosity of the radical polymerizable resin composition.
[0021] The (meth)acrylic acid used as a raw material here is not particularly limited and any known (meth)acrylic acid can be used. In this specification, "(meth)acrylic acid" means "methacrylic acid" and "acrylic acid", and "(meth)acrylate" means "methacrylate" and "acrylate".
[0022] The epoxy (meth)acrylate (A) can be obtained by reacting the bisphenol A type epoxy resin and (meth)acrylic acid in the presence of a known esterification catalyst and polymerization inhibitor, for example, at a temperature range of 80 to 140° C. As the esterification catalyst, at least one selected from the group consisting of a compound containing tertiary nitrogen, a phosphorus compound, an amine salt, and an antimony compound is preferable, and a compound containing tertiary nitrogen is more preferable.
[0023] The content of this epoxy (meth)acrylate (A) is not particularly limited, but is preferably from 10 to 90 mass %, and more preferably from 20 to 80 mass %, in the radical polymerizable resin composition of this embodiment.
[0024] <Aliphatic (meth)acrylate monomer (B)> The aliphatic (meth)acrylate monomer (B) used in this embodiment is a (meth)acrylate monomer in which an aliphatic substituent is bonded to a (meth)acryloyl group, and acts as a reactive diluent. By containing this aliphatic (meth)acrylate monomer (B), the viscosity of the radical polymerizable resin composition can be reduced, and the impregnation of the radical polymerizable resin composition into reinforcing fibers, etc. can be improved.
[0025] In the aliphatic (meth)acrylate monomer (B), the aliphatic substituent may be a chain or alicyclic hydrocarbon group or a group in which a part of the carbon atoms of the hydrocarbon group is replaced with a heteroatom such as oxygen or nitrogen. The aliphatic substituent may have an unsaturated bond, but is preferably a group consisting of a saturated bond. The aliphatic substituent is more preferably a saturated hydrocarbon group.
[0026] Since the aliphatic (meth)acrylate monomer (B) is contained as a diluent as described above, the number of carbon atoms is preferably 11 or less, more preferably 10 or less, and even more preferably 9 or less, in that the viscosity of the radically polymerizable resin composition can be well adjusted. The number of carbon atoms is preferably 4 or more, more preferably 5 or more, and even more preferably 6 or more.
[0027] Examples of the aliphatic (meth)acrylate monomer (B) include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate.
[0028] Among these, n-butyl(meth)acrylate, i-butyl(meth)acrylate, and t-butyl(meth)acrylate are preferred from the viewpoints of dilutability, drying property, resin properties, etc. From the viewpoints of dilutability and drying property, n-butyl(meth)acrylate and i-butyl(meth)acrylate are more preferred, and from the viewpoint of improving hot water resistance, t-butyl(meth)acrylate is more preferred.
[0029] Also, as the aliphatic (meth)acrylate monomer (B), a (meth)acrylic acid ester compound having two or more (meth)acryloyl groups in the molecule can be used. Specific examples thereof include (meth)acrylic acid esters of various glycols such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerin di(meth)acrylate, and 2-hydroxy-3-acryloyloxypropyl (meth)acrylate. The above-mentioned polymerizable monomers may be used alone or in combination of two or more kinds depending on the application.
[0030] The content of this aliphatic (meth)acrylate monomer (B) is not particularly limited, but the mass ratio of the epoxy (meth)acrylate (A) to the aliphatic (meth)acrylate monomer (B) [(A) / (B)] is preferably in the range of 30 / 70 to 80 / 20, more preferably 40 / 60 to 60 / 40.
[0031] <Allyl ether compound (C)> The allyl ether compound (C) used in the present embodiment is a compound having an allyloxy group that functions as a polymerizable monomer. The allyl ether compound is not particularly limited as long as it has an allyloxy group.
[0032] However, if the molecular weight of the allyl ether compound is too large, the mass of the allyl ether compound blended in the radical polymerizable resin composition becomes large, and the viscosity of the resin composition becomes high, which may affect the workability when carrying out lining, etc. Therefore, the molecular weight of this allyl ether compound (C) is preferably 500 or less, more preferably 400 or less, and even more preferably 300 or less. In addition, the lower limit of the molecular weight of the allyl ether compound is not particularly limited, but may be, for example, 100 or more.
[0033] Examples of the allyl ether compound (C) include compounds having three allyloxy groups in the molecule, such as trimethylolpropane triallyl ether, glycerin triallyl ether, pentaerythritol triallyl ether, ditrimethylolpropane triallyl ether, diglycerin triallyl ether, erythritol triallyl ether, xylitol triallyl ether, dipentaerythritol triallyl ether, sorbitol triallyl ether, and inositol triallyl ether; and compounds having four allyloxy groups in the molecule, such as pentaerythritol tetraallyl ether, ditrimethylolpropane tetraallyl ether, diglycerin tetraallyl ether, erythritol tetraallyl ether, xylitol tetraallyl ether, dipentaerythritol tetraallyl ether, sorbitol tetraallyl ether, and inositol tetraallyl ether. Other examples include xylitol pentaallyl ether, dipentaerythritol pentaallyl ether, dipentaerythritol hexaallyl ether, sorbitol pentaallyl ether, sorbitol hexaallyl ether, inositol pentaallyl ether, inositol hexaallyl ether, phenol novolac-type polyallyl ether, cresol-type polyallyl ether, naphthalene-containing novolac-type polyallyl ether, and diallylaminophenol allyl ether.
[0034] It is believed that the allyl ether compound (C) can combine with oxygen in the air to generate peroxides, suppressing the inhibition of curing of the resin composition in the air and accelerating the curing reaction. That is, the air curing property (drying property) during resin curing is improved. In addition, since a high ether concentration in the allyl ether compound (C) is advantageous in terms of air curing property, the allyl ether compound (C) is preferably pentaerythritol triallyl ether, erythritol triallyl ether, xylitol tetraallyl ether, etc., in terms of the high allyl ether concentration in the compound.
[0035] The content of this allyl ether compound (C) is not particularly limited, but the molar ratio of the allyloxy group derived from the allyl ether compound (C) to the sum of the (meth)acryloyl group derived from the epoxy (meth)acrylate (A) of this embodiment and the (meth)acryloyl group derived from the aliphatic (meth)acrylate monomer (B) [allyloxy group / (meth)acryloyl group] satisfies the range of 0.01 to 0.5, and more preferably satisfies the range of 0.05 to 0.3.
[0036] When the number of allyloxy groups in the allyl ether compound (C) is decreased and the above-mentioned quantitative ratio becomes too small, there is a concern that sufficient improvement in air curing property cannot be obtained, whereas when the number of allyloxy groups is increased and the above-mentioned quantitative ratio becomes too large, there is a possibility that the hot water resistance (chemical resistance) and the storage property of the resin composition itself will be deteriorated.
[0037] <Other ingredients> The radical polymerizable resin composition of the present embodiment may further contain a methacrylic acid-modified alkoxylated bisphenol in addition to the above components. Examples of the methacrylic acid-modified alkoxylated bisphenol include ethoxylated bisphenol A dimethacrylate. The methacrylic acid-modified alkoxylated bisphenol has a function of lowering the viscosity of the radical polymerizable resin composition.
[0038] The methacrylic acid-modified alkoxylated bisphenol can be obtained by polyaddition reaction of alkylene oxide to bisphenol by a known method, followed by condensation reaction with methacrylic acid or transesterification reaction with methyl methacrylate. In addition, commercially available methacrylic acid-modified alkoxylated bisphenol can be used. The number of moles of polyaddition of alkylene oxide in one molecule is not particularly limited, but is preferably 2 to 10, more preferably 2 to 4. The content of methacrylic acid-modified alkoxylated bisphenol in the radical polymerizable resin composition is preferably 10 to 30% by mass, more preferably 15 to 25% by mass.
[0039] The radical polymerizable resin composition of the present embodiment may contain, as other components, a curing retarder, a curing agent, a curing accelerator, a curing co-accelerator, a photoradical initiator, etc. Depending on the application, these may be added during the synthesis of the epoxy (meth)acrylate resin, may be mixed simultaneously when the epoxy (meth)acrylate resin and the polymerizable monomer are mixed, or may be mixed after the radical polymerizable resin composition is prepared. In particular, the curing retarder that delays curing is preferably added during the synthesis of the epoxy (meth)acrylate resin or when the epoxy (meth)acrylate resin and the polymerizable monomer are mixed, and the curing agent, the curing accelerator, the curing co-accelerator, and the photoradical initiator are preferably mixed immediately before use.
[0040] The curing retarder is blended to prevent gelation during production, ensure pot life during molding, and improve storage stability. Suitable curing retarders include polyhydric phenol curing retarders such as methylhydroquinone, hydroquinone, toluhydroquinone, trimethylhydroquinone, and tertiary butylcatechol, and quinone curing retarders such as parabenzoquinone and toluquinone. The content of the curing retarder in the radical polymerizable resin composition is preferably 0.001 to 0.5% by mass, and more preferably 0.005 to 0.15% by mass.
[0041] Curing agents, curing accelerators, curing co-accelerators, and photoradical initiators are used to quickly obtain a homogeneous cured product during molding. These can be used alone or in combination of two or more, and the type and amount can be selected according to the application.
[0042] Examples of the curing agent include ketone peroxide-based curing agents such as methyl ethyl ketone peroxide and acetyl acetone peroxide, diacyl peroxide-based curing agents such as benzoyl peroxide, peroxyester-based curing agents such as t-butyl peroxybenzoate, hydroperoxide-based curing agents such as cumene hydroperoxide, dialkyl peroxide-based curing agents such as dicumyl peroxide, etc. The content of the curing agent in the radical polymerizable resin composition is preferably 0.05 to 5% by mass.
[0043] Curing accelerators include metal soaps such as cobalt naphthenate, cobalt octylate, cobalt 2-ethylhexanoate, zinc octylate, vanadium octylate, copper naphthenate, and barium naphthenate; metal chelates such as vanadium acetylacetate, cobalt acetylacetate, and iron acetylacetonate; aniline, N,N-dimethylaniline, N,N-diethylaniline, p-toluidine, N,N-dimethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, 4-(N,N-dimethylamino)benzaldehyde, 4-[N Examples of the curing accelerator include N,N-substituted anilines such as N,N-bis(2-hydroxyethyl)amino]benzaldehyde, 4-(N-methyl-N-hydroxyethylamino)benzaldehyde, N,N-bis(2-hydroxypropyl)-p-toluidine, N-ethyl-m-toluidine, triethanolamine, m-toluidine, diethylenetriamine, pyridine, phenylmorpholine, piperidine, N,N-bis(hydroxyethyl)aniline, and diethanolaniline, N,N-substituted-p-toluidine, and amines such as 4-(N,N-substituted amino)benzaldehyde. The content of the curing accelerator in the radical polymerizable resin composition is preferably 0.05 to 5% by mass.
[0044] Examples of the curing promoter include metal soaps such as those of calcium, strontium, barium, and copper, β-diketones such as acetylacetone, ethyl acetoacetate, and dimedone, aromatic tertiary amines such as dimethylaniline, and phosphorus compounds such as triphenylphosphine and 2-ethylhexyl phosphite. The content of the curing promoter in the radical polymerizable resin composition is preferably 0.001 to 1.0% by mass.
[0045] Examples of the photoradical initiator include benzophenone-based photoradical initiators such as benzophenone, benzil, and methyl orthobenzoyl benzoate; benzoin ether-based photoradical initiators such as benzoin alkyl ether; acetophenone-based photoradical initiators such as benzil dimethyl ketal, 2,2-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone, 4'-isopropyl-2-hydroxy-2-methylpropiophenone, and 1,1-dichloroacetophenone; and thioxanthone-based photoradical initiators such as 2-chlorothioxanthone, 2-methylthioxanthone, and 2-isopropylthioxanthone. The content of the photoradical initiator in the radical polymerizable resin composition is preferably 0.1 to 5% by mass.
[0046] The radical polymerizable resin composition of the present embodiment may further contain a wax. Examples of the wax include oxidized waxes such as saturated fatty acids and saturated fatty acid esters, petroleum waxes such as paraffin wax, natural waxes, synthetic waxes, and microcrystalline waxes. The content of the wax in the radical polymerizable resin composition is preferably 0.01 to 10% by mass, and more preferably 0.1 to 2% by mass.
[0047] Furthermore, any additives such as a solvent, a catalyst, a filler, etc. may be added to the radical polymerizable resin composition of the present embodiment depending on the application, within the range that does not impair the effects of the present invention.
[0048] The radical polymerizable resin composition of the present embodiment can be produced by mixing the above-mentioned epoxy (meth)acrylate (A), aliphatic (meth)acrylate monomer (B), allyl ether compound (C), and other optional components by a conventional method.
[0049] The radical polymerizable resin composition thus obtained can be cured by various curing reactions. Examples of the curing method include room temperature curing, heat curing, and photocuring. The radical polymerizable resin composition of this embodiment is preferably cured at room temperature because it does not require special equipment or operations such as heating or light irradiation for curing. The radical polymerizable resin composition of this embodiment contains an allyl ether compound (C) which is a polymerizable monomer. The allyl ether compound (C) has the effect of improving air curing by oxidative polymerization with oxygen in the air, and in this embodiment, by using the monomer, it has been found that the effect of room temperature curing proceeds quickly, although the reaction mechanism is not clear.
[0050] The radical polymerizable resin composition of the present embodiment can be molded by various molding methods. Examples of the molding methods include hand lay-up molding, spray-up molding, casting, filament winding molding, resin transfer molding, back molding, pultrusion molding, preformed matched die molding, and cold press. The radical polymerizable resin composition of the present embodiment is preferably molded by hand lay-up molding.
[0051] In this case, molding can be performed using a material impregnated into reinforcing fibers, and examples of the reinforcing fibers include glass fibers, carbon fibers, aramid fibers, and natural fibers. Hybrid fibers that combine carbon fibers with glass fibers or aramid fibers can also be used. The shape of the reinforcing fibers may be chopped strands or mats thereof, rovings or roving cloths made by weaving rovings, fibers aligned in one direction, and the like. These fibers may be used alone or in combination of two or more.
[0052] <Characteristics of radically polymerizable resin composition and cured resin> The radical polymerizable resin composition obtained as described above can have a relatively low viscosity, and is suitable for general lamination applications such as lining. In this case, the viscosity of the radical polymerizable resin composition at 25°C is preferably 100 to 550 mPa·s. The upper limit of this viscosity is more preferably 500 mPa·s or less, and even more preferably 450 mPa·s or less. By setting the viscosity within this range, the workability is improved when forming a resin layer by repeatedly applying and drying, or when impregnating reinforcing fibers, and the composition is suitable for lining. In addition, the composition is particularly suitable for hand lay-up molding. The viscosity of the radical polymerizable resin composition can be measured in accordance with, for example, JIS K6901:2008 "Viscosity".
[0053] In addition, the radical polymerizable resin composition has good air curing properties in air, which greatly improves the workability when laminating resin layers by repeatedly applying and curing the resin composition, making the composition suitable for general lamination applications such as lining. The air curing property can be evaluated, for example, by leaving the resin composition in an air atmosphere at 25° C. for 16 hours and then checking whether or not there is tack when the resin composition is touched with a finger.
[0054] In addition, the dried and cured radical polymerizable resin composition (resin cured product) preferably has a tensile elongation of 4% or more. With a tensile elongation of 4% or more, defects such as peeling and cracks during resin molding do not occur, and a resin cured product of a desired shape can be stably obtained. A resin composition that can satisfy the above tensile elongation is particularly suitable for lining. The tensile elongation can be calculated, for example, by using a sample processed in accordance with JIS K7164:2005 type IB series B type, using an extensometer in accordance with JIS K7161-1:2014 and JIS K7161-2:2014.
[0055] The cured radically polymerizable resin composition (cured resin) of this embodiment has good hot water resistance (chemical resistance) and the product stability after curing is good. The hot water resistance (chemical resistance) can be evaluated, for example, in accordance with JIS K7171:2022, by measuring the bending strength of a sample before and after a corrosion resistance test, and calculating the property retention rate according to the following formula. (Bending strength value after corrosion resistance test) / (Initial bending strength value (before corrosion resistance test)) x 100 EXAMPLES
[0056] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. Measurements and evaluations in the examples were performed according to the methods described below.
[0057] First, the epoxy (meth)acrylate (A) was synthesized according to the following Synthesis Examples 1 to 3. (Synthesis Example 1) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a gas inlet tube, 662 g of bisphenol A type epoxy resin (Epiclon 850, manufactured by Dainippon Ink and Chemicals, Inc., epoxy equivalent 188), 109 g of bisphenol A, and 0.39 g of triphenylphosphine were charged, and the mixture was reacted at 150°C for 1 hour while stirring and blowing in nitrogen, to obtain a bisphenol A type epoxy resin with an epoxy equivalent of 300 g / eq. Next, 229 g of methacrylic acid (manufactured by Mitsubishi Gas Chemical Co., Inc.) and 0.2 g of methylhydroquinone as a polymerization inhibitor were added, and the mixture was stirred at 90°C while blowing in dry air until it became uniform, to obtain a mixture. The mixture was cooled to 60°C, 2.0 g of 2-methylimidazole was added, and the mixture was heated to 130°C and reacted for 3 hours to obtain a bisphenol A type epoxy methacrylate (A-1).
[0058] (Synthesis Example 2) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a gas inlet tube, 647 g of bisphenol A type epoxy resin (Epiclon 850, manufactured by Dainippon Ink and Chemicals, Inc., epoxy equivalent 188), 199 g of bisphenol A, and 0.42 g of triphenylphosphine were charged, and the mixture was reacted at 150°C for 1 hour while stirring and blowing in nitrogen, to obtain a bisphenol A type epoxy resin with an epoxy equivalent of 500 g / eq. Next, 153 g of methacrylic acid (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 0.2 g of methylhydroquinone as a polymerization inhibitor were added, and the mixture was stirred at 90°C while blowing in dry air until it became uniform, to obtain a mixture. The mixture was cooled to 60°C, 2.0 g of 2-methylimidazole was added, heated to 130°C, and reacted for 3 hours to obtain bisphenol A type epoxy methacrylate (A-2).
[0059] (Synthesis Example 3) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a gas inlet tube, 823 g of brominated bisphenol A type epoxy resin (Epiclon 153, manufactured by Dainippon Ink and Chemicals, Inc., epoxy equivalent 400) was charged, and the mixture was melted by heating to 100°C. Then, while blowing in air, 177 g of methacrylic acid (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 1 g of monomethyl ether hydroquinone as a polymerization inhibitor were added under stirring, and while blowing in dry air, the mixture was stirred at 90°C until it became uniform, to obtain a mixture. 1 g of 2-methylimidazole was added to the mixture, which was then heated to 120°C and reacted for 3 hours to obtain brominated bisphenol A type epoxy methacrylate (A-3).
[0060] (Examples 1 to 4, Comparative Examples 1 to 4) Using the bisphenol A type epoxy methacrylate (A-1) obtained in Synthesis Example 1, the bisphenol A type epoxy methacrylate (A-2) obtained in Synthesis Example 2, and the brominated bisphenol A type epoxy methacrylate (A-3) obtained in Synthesis Example 3, as well as the aliphatic (meth)acrylate monomer (B) and the allyl ether compound (C), resin compositions were prepared according to the formulations shown in Table 1. The bisphenol A type epoxy acrylate (A) used in Comparative Examples 2 and 3 was an epoxy acrylate obtained in the same manner as in Synthesis Example 1 above, except that Epiclon 850 was used as it was as the raw epoxy resin. For each of the resulting resin compositions, the liquid properties, cast plate properties, and air curing properties were measured, and the results are also shown in Table 1. The properties were measured and calculated as follows.
[0061] <Viscosity> 180 g of each resin composition was weighed out and placed in a 225 mL cylindrical glass bottle, and immersed in a water bath adjusted to 25° C. for 30 minutes or more. After confirming with a thermometer that the temperature of the resin composition was 25° C., the viscosity was measured with a single cylindrical rotational viscometer. The measurement method was in accordance with JIS K6901:2008 "Viscosity".
[0062] [Cast plate characteristics] For 100% by mass of the resin composition prepared in each Example and Comparative Example, an appropriate amount of hydroquinone was added as a polymerization inhibitor so that the gelation time at 25°C was about 30 minutes, 0.5% by mass of "Nikka Octix (registered trademark) Cobalt (8%)" manufactured by Nippon Kagaku Sangyo Co., Ltd. was added and dissolved as a curing accelerator, and then 1% by mass of "Permec N" manufactured by NOF Corporation was added and dissolved as an organic peroxide. The resin composition was poured into a 3 mm thick flat tempered glass cell with cellophane for release attached, cured at room temperature for 16 hours, and further post-cured at 120°C for 2 hours to prepare a cast plate. The tensile elongation and hot water resistance of this cast plate were measured and evaluated as follows.
[0063] <Tensile elongation> The above cast plate was processed in accordance with JIS K7164:2005 Type IB Series B type, and a tensile test was performed at a test speed of 1 mm / min indoors at an air temperature of 23°C. The tensile elongation was calculated using an extensometer in accordance with JIS K7161-1:2014 and JIS K7161-2:2014. A tensile elongation of 4.0% or more is considered acceptable.
[0064] <Hot water resistance> The bending strength was measured at 1.5 mm / min according to the procedure of JIS K7171:2022. Next, the above-mentioned cast plate was processed into 100 mm x 80 mm, immersed in pure water at 80 °C for 3 months, and then the bending strength was measured again and calculated using the following formula. (Bending strength value after corrosion resistance test) / (Initial bending strength value) x 100 The evaluation criteria for hot water resistance were as follows: ⊚: physical property retention rate of 80% or more, ◯: physical property retention rate of 60% or more but less than 80%, and ×: physical property retention rate of less than 60%.
[0065] <Air curing> To 100% by mass of the resin composition prepared in the above Examples and Comparative Examples, an appropriate amount of hydroquinone was added as a polymerization inhibitor so that the gelation time at 25 ° C. was about 30 minutes, 0.5% by mass of "Nikka Octix (registered trademark) Cobalt (8%)" manufactured by Nippon Kagaku Sangyo Co., Ltd. was added and dissolved as a curing accelerator, and then 1% by mass of "Permec N" manufactured by NOF Corporation was added and dissolved as an organic peroxide. Three 10 cm x 10 cm chopped strand mats (#450: manufactured by Nitto Boseki Co., Ltd.) were laminated on a PET film with 31.5 g of the resin composition (glass content 30% by mass) and cured at 25 ° C. The air curing property was confirmed by touching the surface condition with a finger 12 hours after lamination. The evaluation criteria for air curing property were ◯ if it was not sticky when touched with a finger, and × if it was sticky.
[0066] [Table 1]
[0067] From the above, it was found that the radical polymerizable resin compositions of the Examples are non-styrene resin compositions that do not use styrene as a reactive diluent, yet are capable of providing the cured resin with good properties in both tensile elongation and hot water resistance. Furthermore, the viscosity of this radically polymerizable resin composition can be reduced and it has good air curing properties, making it suitable for use as a lining.
Claims
1. an epoxy (meth)acrylate (A) which is an ester compound made from a bisphenol A type epoxy resin and (meth)acrylic acid; an aliphatic (meth)acrylate monomer (B); An allyl ether compound (C), A radical polymerizable resin composition comprising: The radical polymerizable resin composition, wherein the bisphenol A type epoxy resin has an epoxy equivalent of 200 to 700.
2. 2. The radical polymerizable resin composition according to claim 1, wherein a mass ratio [(A) / (B)] of the epoxy (meth)acrylate (A) to the aliphatic (meth)acrylate monomer (B) is 30 / 70 to 80 / 20.
3. 2. The radical polymerizable resin composition according to claim 1, wherein a molar ratio of the allyloxy group derived from the allyl ether compound (C) to the total of the (meth)acryloyl group derived from the epoxy (meth)acrylate (A) and the (meth)acryloyl group derived from the aliphatic (meth)acrylate monomer (B) [allyloxy group / (meth)acryloyl group] is 0.01 to 0.
5.
4. 2. The radical polymerizable resin composition according to claim 1, wherein the aliphatic (meth)acrylate monomer (B) is an aliphatic (meth)acrylate monomer having a saturated aliphatic hydrocarbon group.
5. The radical polymerizable resin composition according to claim 4 , wherein the aliphatic (meth)acrylate monomer (B) has 11 or less carbon atoms.
6. The radical polymerizable resin composition according to claim 1 , wherein the allyl ether compound (C) has a molecular weight of 500 or less.
7. The radical polymerizable resin composition according to claim 1, further comprising at least one selected from the group consisting of a curing agent, a curing accelerator, a curing co-accelerator and a photoradical initiator.
8. The radical polymerizable resin composition according to claim 1 , which is for hand lay-up molding.
9. A molded article comprising a cured resin product of the radical polymerizable resin composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Curable resin composition, concrete-coated composition, and lining material
JP2014095002A
Resin composition, and fiber-reinforced resin material made of the resin composition
JP2023055303A